Functionalized graphene oxide loaded with protocatechuic acid for passive and active delivery systems - Buskaran, Kalaivani (2020)
Cancer presents as one of the biggest health threat in the world. Chemotherapeutic agents which are commonly used to treat cancer are lacking in its specificity, resulting in harming and injuring healthy tissues in trivial treatment efficacy. To overcome these obstacles, considerable efforts have been made in ensuring effective cancer therapy particularly utilizing nanotechnology. Recent studies have shown that functionalized graphene oxide (GO) as nanocarrier with biocompatible polymers lead to higher loading efficacy and better stability with lower cellular toxicity. This study is aimed to explore and investigate cellular uptake of passive and active targeting of functionalized graphene oxide coated with folic acid nanocomposite for cancer therapy. The nanodrug delivery system was designed with an anticancer compound like protocatechuic acid (PCA) and chlorogenic acid (CA) on functionalized graphene oxide conjugated polyethylene glycol as the nanocarrier (GOP) and coated with folic acid for targeting cancer cells. The physicochemical parameters such as size, morphology, drug encapsulation and drug release profile of these compounds were thoroughly characterized. The nanocarrier and nanocomposites were screened against normal and cancer cells using MTT assay for 72 h within the tested range of concentration and duration. Graphene oxide conjugated with polyethylene gycol, loaded with protocatechuic acid and coated with folic acid (GOP-PCA-FA) showed the optimum IC50 value at lowest concentration of 18.89 μg/mL towards HepG2 cells after 72 h of treatment. Besides, folate receptor coated nanocomposite were found to be highly expressed in HepG2 cells compared to HT29 cells. The nanocomposite explored as a promising nano delivery strategy by enhancing the cellular uptake and localization of nanocomposite to improve therapeutic efficacies. Transmission electron microscope (TEM) was utilize to observe the nanocomposites cellular uptake and morphological changes which occurred by post treatment on HepG2 cell from 24 h to 72 h. Fluorescein isothiocyanate (FITC) was conjugated to GOP-PCA-FA which confirms the intracellular localization and accumulation into cell at 48 h later. Subsequent anticancer toxicity activities were evaluated among pristine protocatechuic acid, GOP-PCA (passive target) and GOP-PCA-FA (active target) drug delivery. All the experiments were conducted at IC50 value of pristine protocatechuic acid (38 µg/mL) on HepG2 cells. The cell migration of HepG2 treated nanocomposites shows significant cell exclusion zone. Clonogenic assay was carried out to examine the colony forming ability of treated cells on potential chronic toxicity. Lactate dehydrogenase assay shows dose-dependent manner severity on membrane integrity of HepG2 cells. The Annexin V/PI flow cytometry analysis showed that nanocomposites induces late apoptosis in HepG2 cells. Following the intervention of nanocomposites, the cell cycle arrest was ascertained at G2/M phase. Mitochondrial membrane potentials were evaluated to determine the extent of mitochondrial disruption including changes in membrane potential caused by nanocomposites. The level of free radical species production was significantly increased in nanocomposites treated HepG2 cells. The proteomic profiling array exposed the pro-apoptotic proteins such as BAD, BAX, pro-caspase-3, cytochrome-c, p21 and p53 were upregulated and anti- apoptotic proteins Bcl-2, Bcl-xL and HSP70 were downregulated upon GOP- PCA-FA treatment in HepG2 cells. This data was confirmed by conducting RT- qPCR in identifying the changes in gene expression of HepG2 cells. In conclusion, GOP-PCA-FA nanocomposite treated HepG2 cells exhibit less toxicity, better cellular uptake and localization with significant anticancer activity compared to pristine protocatechiuc acid or GOP-PCA nanocomposite due to the utilization of active targeting drug delivery system.